Learning at the Crossroads of Theory and Practice
VIII, 252 p.
Keywords: Core concepts in education are changing. For example, professional performance or expertise is not uniquely the fruit of specialist knowledge acquired at professional schools, but the sum of influences exerted by a complex web of continuous learning opportunities for which an individual is well (or ill) prepared by their schools and their workplace. The key contributory factors to professional expertise are how professional schools connect to professional practice, how schools prepare graduates for continuous learning, and how the workplace endorses continuous development. Thus, the question this volume addresses—how to design learning and working environments that facilitate the integration of these three elements—is at the heart of contemporary pedagogical theory. The authors also ask a second vital question: how do we educate learners that go on to maximize their life’s learning opportunities by regulating their own ongoing learning? Learning at the Crossroads of Theory and Practice argues that with the theory of learning at a crossroads, this is an unprecedented opportunity for learning about learning. The book sheds light on different elements of this challenge: integrating theory and practice in business education, generating and fully exploiting workplace learning opportunities, and enriching our classrooms by coupling theoretical knowledge with the richness of real-life experience.